Results of percutaneous closure with device in congenital heart disease of the atrial septal defect type (International Journal of Medical and Surgical Sciences, 2022)
Congenital Interatrial Septal Defects (TEA) are among the most common Congenital Heart Diseases in the population, where Atrial Septal Defect stands out, which is produced by a left-right short circuit that provides greater survival and less morbidity and mortality. The objective was to determine the results of Percutaneous Closure with a Device in Congenital Heart Disease of the Atrial Communication type at the Carlos Andrade Marín Specialty Hospital (Quito) in the Hemodynamics service from January 2009 to July 2019. It is a retrospective descriptive cross-sectional study . With a population of 122 cases from the AS400 registry. Thus, it was determined: there is a female predominance in a ratio of 2:1, the ranges for defect intervention were 5.5 mm to 35 mm, post-procedure pulmonary artery pressures (systolic 18-25 mmHg and diastolic 6-10 mmHg) in 95% of patients, ventricular overload in 76% in pre-procedure patients. Concluding that 96% of our population has a significant post-procedure improvement
Keywords: Atrial septal defect; pulmonary hypertension; right overload